Exploring the Impact of Social Interactions on Academic Achievement among Learners at the National Open University of Nigeria (2025)
It has become necessary to integrate both in-person and virtual learning exchanges in order to address the issue of learners feeling disconnected and uncomfortable while studying remotely. Based on this, the study examined the effects of social interactions (face-to-face tutorial meetings and online interactions) on learners’ academic achievement in the institution. The study design used was a descriptive survey. 200 students were chosen at random from the colleges of law, arts and social science, business and human resources, education, science and technology, and the centre for continuing education, making up the population of 100–500 level students. We used the Perceived Social Interaction on Learners' Academic Achievement in the National Open University of Nigeria Scale (r=.82) as the study's questionnaire, which consisted of thirty questions. Descriptive statistics and multiple regression were used to examine the data. The findings of the research showed that social interactions—both in-person tutorial sessions and online interactions—co-accounted for 02.2% of the variation in students' academic achievement and had no discernible impact on it (F (2,189) = 2.135; R2 = 0.022). Based on the study's results, the administration of the National Open University of Nigeria was advised to include social media, Google apps, and all learning technologies in order to support both in-person and virtual interactions. This proactive approach would ensure learners' participation and retention in the institution. This unique research on social connections and students' academic progress was carried out at the National Open University of Nigeria.